Biogeography of amphi-adriatic Gentianella crispata (Gentianaceae): a northern refugium and recent trans-adriatic migration. (7th July 2022) - Reich, Dieter; Flatscher, Ruth; Pellegrino, Giuseppe; Hülber, Karl; Wessely, Johannes; Gattringer, Andreas; Greimler, Josef
Abstract: The Balkan Peninsula as one of Europe's biodiversity hotspots came into the focus of biogeographic research during the last decade, but the phylogeography of its mountain flora still remains widely unexplored. To investigate historical and future range dynamics within Gentianella crispata, a typical plant of mountainous grasslands sub-endemic to the Balkan Peninsula with a single known population in southern Italy, we combine molecular analyses based on cpDNA sequence and amplified fragment length polymorphism data with species distribution models. In the western Balkan, we found a distinctly separated cluster at the northern edge of the species' distribution range. The split towards the less structured southern populations is located at the Neretva canyon, a pattern repeatedly reported before. This finding is clearly in line with the refugia-within-refugia hypothesis assuming more than one Pleistocene refugium on the Balkan Peninsula. The Italian population was found to be closely related to populations in the central to southern Dinaric mountains indicating a recent, possibly human-mediated migration event. Niche models for future climate scenarios forecast a severe loss of climatically suitable areas, especially in the southern parts of the range, pointing at deteriorating effects of climate warming for those mountainous grassland habitats in southern Europe, which harbour G. crispata .